2021
DOI: 10.1093/sleep/zsab282
|View full text |Cite
|
Sign up to set email alerts
|

The association between obstructive sleep apnea and sleep spindles in middle-aged and older men: a community-based cohort study

Abstract: Study objectives Sleep spindles show morphological changes in obstructive sleep apnea (OSA). However, previous small studies have limited generalisability, leaving associations between OSA severity measures and spindle metrics uncertain. This study examined cross-sectional associations between OSA severity measures and spindle metrics among a large population-based sample of men. Methods Community-dwelling men with no previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
(56 reference statements)
0
11
0
Order By: Relevance
“…As described previously (Parker et al, 2022; Parker, Appleton, et al, 2021; Parker, Melaku, et al, 2021), participants underwent home‐based eight‐channel ambulatory PSG (Embletta X100, Embla Systems, Broomfield, Colorado, USA), which recorded electrical brain activity (electroencephalography [EEG], F4‐M1) and left electro‐oculography with 12‐bit signal resolution, 200 Hz sampling rate, and band‐pass filters (0.3–35 Hz) together with submental electromyography, nasal cannula pressure, thoracic and abdominal motion, finger pulse oximetry, and body position. Trained staff set‐up and attached the PSG equipment and obtained anthropometric measures (height, weight, and body mass index [BMI, kg/m 2 ]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described previously (Parker et al, 2022; Parker, Appleton, et al, 2021; Parker, Melaku, et al, 2021), participants underwent home‐based eight‐channel ambulatory PSG (Embletta X100, Embla Systems, Broomfield, Colorado, USA), which recorded electrical brain activity (electroencephalography [EEG], F4‐M1) and left electro‐oculography with 12‐bit signal resolution, 200 Hz sampling rate, and band‐pass filters (0.3–35 Hz) together with submental electromyography, nasal cannula pressure, thoracic and abdominal motion, finger pulse oximetry, and body position. Trained staff set‐up and attached the PSG equipment and obtained anthropometric measures (height, weight, and body mass index [BMI, kg/m 2 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Three standardised, validated, and well‐established cognitive tests, described previously (Parker et al, 2022; Parker, Appleton, et al, 2021; Parker, Melaku, et al, 2021), were administered during the 2007–2010 follow‐up and repeated at the 2018–2019 follow‐up examination, including TMT‐A and ‐B and the 30‐point MMSE.…”
Section: Methodsmentioning
confidence: 99%
“…However, previous studies on patients with OSAS mainly focus on the changes in oscillatory neural activity in a single brain region or a single frequency band without considering the synchronization between different brain regions [ 13 , 22 ]. Previous studies have also investigated the relationship between spindle parameters and memory ability [ 23 ]. These studies focused on time domain characteristics such as number, density and frequency, which could not fully reflect the physiological characteristics of the sleep spindle.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggest that quantitative EEG may provide more sensitive markers for identifying patient phenotypes at risk for adverse health outcomes compared with conventional sleep scoring. 17 , 18 , 19 , 20 However, few studies have investigated the association between sleep microstructure and future development of hypertension. One study performed in a small sample of middle‐aged women showed that those with low delta power during NREM sleep may be at increased risk of developing hypertension.…”
mentioning
confidence: 99%
“…One study performed in a small sample of middle‐aged women showed that those with low delta power during NREM sleep may be at increased risk of developing hypertension. 21 However, obstructive sleep apnea was not controlled for, which clearly impacts quantitative EEG, 19 and thus may have confounded the association with hypertension.…”
mentioning
confidence: 99%